Contagion channels of the financial crisis towards Maghreb countries. (17th June 2019) - Otmani, Abdelhafid; Abadli, Riad
Financial crises tend to spread, like epidemics. In this paper, we try to identify the main transmission channels of the 'subprimes' global financial crisis towards Maghreb countries in order to better apprehend the impact of this crisis and its propagation, as well as the vulnerability of each country and the affected areas. In this article we will approach and retain the main transmission channels, the interdependence commercial and financial channel spill-over effect (Masson, 1998), then the similarity effects channel (Ahluwalia, 2000). We will also pass through the monsoonal effect (Masson, 1998). And finally the common joint creditor channel. As a result, the analysis of the three Maghreb countries (Algeria, Morocco, Tunisia) shows us that the financial and economic crisis, originating from the USA, has taken various transmission channels in one way or another in the spread of this crisis to reach those countries that were not spared.